″Vocational training of specialists in publishing and printing in higher educational institutions: status, problems, ways of improvement″ - Denisenko, S. (Problems of Engineer-Pedagogical Education, 2018)
One of the main problems of higher education in the field of publishing and printing is to bring the level of knowledge, skills and competencies of future specialists in line with the needs of this high-tech information industry. Successful solution of the stated problem is possible on condition that there is a complete picture of both the state of the sphere of activity itself and that of higher vocational education. This will allow education to meet the requirements of the labor market. The article deals with defining the current state of vocational training of specialists in publishing and printing in higher educational institutions. The requirements for future specialists that are put forward by the modern publishing and printing industry are determined. On the basis of the analysis of scientific works and the author’s own experience, the main problems which complicate the quality training of future specialists are identified. The article also describes possible ways to solve the problems identified, which can help overcome the contradiction between the inadequate training that students receive and the requirements of the modern publishing industry.